FATORES CRITICOS DE SUCESSO DO STARTUP DE UM SISTEMA DE SEGURANÇA DA INFORMAÇÃO PARA O INMETRO E A QUALIDADE PERCEBIDA PELO USUÁRIO - Mello, Marcio Luiz Liduino de (2006)
Considered in actuality to be an indispensable factor for business administration, information has not always been considered by organizations as a resource. Considered in the 1950's as a necessary bureaucratic requirement, information in the 1960's and 1970's came to be seen as a support for general business goals. In the 1970's and 1980's it began to be treated as a factor for control and management for the entire organization, but it was only beginning in the 1990's that it was recognized as a strategic resource, a source of competitive advantage to guarantee the survival of the business, and this vision persists even today. Still evident in the actual organizational environment, information became an indispensable tool for business managers in all levels of business, applied to decision-making processes, and considered as something that must be protected. Therefore, with the identification of information considered a more and more important activity in order to obtain competitive advantages, the need was verified to complete a study to identify the Critical Success Factors (CSF) for the initiation (start-up) of an Information Security System for INMETRO and its Relationship with Perceived Quality for the user. The study is based on the prognostics raised by Porter (1986) about the stages of the life cycle of products and analysis of the evolution of industry and the product. From these prognostics, there also was developed a group of CSF to be validated for a structured questionnaire and applied through field research/survey. Beyond that, there must be a search for a measurement of the users perception of the quality of service provided on a SERVQUAL scale, following the orientation of Parasuraman et al (1988).